2004
DOI: 10.1002/eji.200425598
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT costimulates CD40 triggering and induces immunoglobulin secretion; a novel key partner in T cell‐dependent B cell terminal differentiation

Abstract: The T cell-dependent differentiation and function of B lymphocytes are tightly regulated by TNF ligands (L) and receptors interactions, such as CD40/CD40L, CD27/CD70 and CD134/ CD314L. The LIGHT/HVEM system [homologous to lymphotoxin, inducible expression, competing for GpD of herpes virus, that binds to the herpes virus entry mediator (HVEM), and is expressed on activated T lymphocytes) focused our attention since HVEM has a large distribution that, in addition to T cells, DC or NK, includes tumor and normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 16 publications
0
51
1
Order By: Relevance
“…As previously reported, CD40L did not induce B-CLL cell death (22.672%). Finally, we also tested CD40L/LIGHT costimulation because we had previously shown that these two molecules act in cooperation for B-lymphocyte proliferation [17]. Here, CD40L/LIGHT costimulation gave a similar effect to LIGHT alone; thus neither does CD40L appear to cooperate with LIGHT to induce cell death nor hinders it.…”
Section: Light and Hvem Mab Induces Death Of B-cll Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…As previously reported, CD40L did not induce B-CLL cell death (22.672%). Finally, we also tested CD40L/LIGHT costimulation because we had previously shown that these two molecules act in cooperation for B-lymphocyte proliferation [17]. Here, CD40L/LIGHT costimulation gave a similar effect to LIGHT alone; thus neither does CD40L appear to cooperate with LIGHT to induce cell death nor hinders it.…”
Section: Light and Hvem Mab Induces Death Of B-cll Cellsmentioning
confidence: 99%
“…[23]. In this study we investigated the effects of LIGHT in hematopoietic malignancies and we chose to focus on B-CLL, given the strong expression of HVEM in these cells and our previous results on the importance of LIGHT in the physiology of B lymphocytes [17]. Thus, to explore the impact of LIGHT in this lymphoid malignancy, we stimulated B-CLL cells with an anti-HVEM mAb and performed a QRT-PCR global analysis of the expression of a large panel of genes.…”
Section: Hvem Induces Tnf-a Production: Synergization On Hvem-cell Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies in vitro showed that LIGHT induces T cell proliferation, IFN-γ secretion and NF-B activation (101,102). LIGHT also cooperates with CD40 ligand (CD154) contributing to DC maturation (103)(104)(105). LIGHT induces the …”
Section: Lightmentioning
confidence: 99%